The effect of adding robot-assisted hand rehabilitation to conventional rehabilitation program following stroke: A randomized-controlled study - AKYÜZ, GÜLSEREN DERYA (My University, 2022)
© 2022 All right reserved by the Turkish Society of Physical Medicine and Rehabilitation.Objectives: This study aimed to investigate the effectiveness of adding robot-assisted hand therapy (HandTutor) to conventional rehabilitation program compared to a conventional rehabilitation program alone in stroke survivors. Patients and methods: Between March 2012 and December 2012, a total of 33 stroke patients (21 males, 12 females; median age: 56 years; range, 38 to 73 years) were included in this prospective, randomized-controlled study. The patients were randomly divided into two groups as experimental (n=16) and control (n=17). Both groups received conventional rehabilitation for 3 h/day, for two days/week, totally for five weeks, while the experimental group received additional 1-hour robot-assisted hand therapy during each session. Outcome measures were the Fugl-Meyer Assessment, Box and Block Test, Nine-Hole Peg Test, Jebsen-Taylor Hand Function Test, grip strength, and pinch strength. All patients were assessed at baseline, at the end of the treatment, and three months after the treatment. Results: Both groups showed statistically significant improvements in all the parameters (p0.05). The changes between baseline and three-month follow-up after the treatment revealed that adding robot-aided hand therapy led to greater changes in all the parameters related to functional activities and muscle strength, except for the Fugl-Meyer Assessment. Conclusion: Adding robot-assisted therapy to conventional rehabilitation may provide greater changes in upper extremity rehabilitation of subacute stroke patients compared to conventional rehabilitation program alone.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Rehabilitation; Functional activities; muscle strength; robot-assisted therapy; stroke; Functional activities; muscle strength; robot-assisted therapy; stroke.